2017
DOI: 10.1186/s13756-016-0155-y
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of antibiotic-resistant Enterobacteriaceae in hospitalised children in tertiary hospitals in Harare, Zimbabwe

Abstract: BackgroundExtended-spectrum β-lactamase-producing and gentamicin resistant Enterobacteriaceae are increasingly recognised as a major cause of infection in low-income countries. We assessed the prevalence of gastrointestinal carriage of these bacteria in hospitalised children in Harare, Zimbabwe.MethodsWe conducted a cohort study in paediatric inpatients at two tertiary-referral hospitals between May and July 2015. Rectal swabs and faecal samples were collected within 24 h of admission and further follow-up sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…From the study findings, carbapenem resistance by Enterobacteriaceae was very low (i.e., < 1%) throughout the 6 years in this study. The findings are consistent with Magwenzi et al 2017 who reported a low prevalence of carbapenem-resistant Enterobacteriaceae of 1% in Harare [17]. Carbapenems are therefore a treatment of choice for ESBL positive infections.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…From the study findings, carbapenem resistance by Enterobacteriaceae was very low (i.e., < 1%) throughout the 6 years in this study. The findings are consistent with Magwenzi et al 2017 who reported a low prevalence of carbapenem-resistant Enterobacteriaceae of 1% in Harare [17]. Carbapenems are therefore a treatment of choice for ESBL positive infections.…”
Section: Discussionsupporting
confidence: 90%
“…Our study reveals statistically significant increases in the prevalence of extended-spectrum beta-lactamase (ESBL) producing Enterobacteriaceae . Magwenzi et al 2017 reported ESBL carriage in 52% of patients before hospital admission, suggesting endemic ESBL carriage in Harare [17]. Other authors have explained the increasing prevalence of ESBL producing Enterobacteriaceae in multiple regions as representing the global expansion of ESBL-producing clones [18].…”
Section: Discussionmentioning
confidence: 99%
“…The main concern of MDROs intestinal carriage is the acquisition of MDRO caused infections with limited therapeutic options (Magwenzi et al, 2017). In addition, as the carriage can last from months to years, the asymptomatic colonization of MDROs constitute a potent reservoir for transmission and dissemination (Decker et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…This is consistent with other studies which estimated the prevalence of ESBL producing Enterobacteriacae in Zimbabwe to be between 20 and 40 %. [ [33] , [34] , [35] ] Proteus species showed increased levels of resistance with half of the isolated Proteus species being ESBL positive and one [ 1 ] isolate being resistant to carbapenems (a CPE). A third of E. coli isolates and 18% of Klebsiella species isolates were ESBL producing organisms.…”
Section: Discussionmentioning
confidence: 99%